Assessing Short-term Flood Impact on Land Use Dynamics in Iran’s Central Zagros: A Case Study of Sefid Kuh Protected Area - Soheyl Moradi; Hossein Moradi; Jafar Dolatshah; Azita Rezvani (Landscape Online)
Floods are extreme events that can alter the land cover and land use patterns in mountainous regions, with significant consequences for biodiversity, ecosystem services, and human well-being. However, there is a lack of comprehensive and integrated studies on the short-term and long-term effects of floods on land cover dynamics in the Central Zagros region, which is a climate change hotspot and a protected area with rich flora and fauna. In this study, we aimed to assess the effects of floods on land cover changes and transitions in the Sefid Kuh Protected Area, Lorestan Province in Iran, using temporal satellite imagery from Landsat 8, land-use/land-cover change detection and fragmentation analysis, and landscape pattern indices. We also conducted fieldwork and interviews to evaluate the impact of floods on land cover from the ground and from the local people’s perspectives. Our results showed that floods caused significant disturbances and shifts in different land cover classes, such as Thin Woodlands, Thick Woodlands, Agriculture, Rock, and Snow. For the landscape pattern indices the Shannon’s Diversity Index (SHDI), Interspersion and Juxtaposition Index (IJI), Patch Density (PD), Edge Density (ED), Largest Patch Index (LPI), Aggregation Index (AI), Percentage of Land Area (PLAND), Number of Patches (NP), Total Edge (TE), Landscape Shape Index (LSI), and Splitting Index (SPLIT) have been used. Results revealed that floods reduced the diversity and heterogeneity of the landscape, increased the fragmentation and isolation of forest patches, and enhanced the aggregation and clumpiness of bare soil patches. These changes have implications for the resilience and adaptation of the study area to future flood hazards and climate change.